2003
DOI: 10.1046/j.1600-6143.2003.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic (vs. Open) Live Donor Nephrectomy: A UNOS Database Analysis of Early Graft Function and Survival

Abstract: Our data suggests that lap nephrectomy is associated with slower early graft function. Rejection rates and short-term graft survival, however, were similar for lap and open graft recipients. Further prospective studies with longer follow up are necessary to assess the potential impact of the laparoscopic procurement mode on early graft function and long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 34 publications
5
58
1
1
Order By: Relevance
“…In line with these findings, it has been shown that recipients of laparoscopically procured kidneys had higher short-term serum Cr compared to recipients of kidneys procured by open technique [7,19].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In line with these findings, it has been shown that recipients of laparoscopically procured kidneys had higher short-term serum Cr compared to recipients of kidneys procured by open technique [7,19].…”
supporting
confidence: 53%
“…In line with this hypothesis, several investigators have reported slower early post-transplant function for laparoscopically retrieved (vs. open) grafts as measured by poor early graft function (EGF) rates [7,8]. This is important because even mild to moderate early graft dysfunction can have a negative impact on long-term graft survival [9].…”
Section: Introductionmentioning
confidence: 95%
“…Hence, it is not surprising that some studies of adult recipients of live donor kidney grafts showed slower early graft function for laparoscopic (vs. open) donor kidneys (11)(12)(13). For pediatric recipients, the scarce available data on the potential impact of laparoscopic (vs. open) nephrectomy are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…From the recipient standpoint, multiple reports have demonstrated equivalent patient and graft survival (2,3). From the donor's perspective, complication rates and lengths of hospital stay have been shown to be lower when compared to the open approach (4).…”
Section: Introductionmentioning
confidence: 99%